Ações da Odontologia em Consultas de Puericultura na Estratégia Saúde da Família - Macambira, Dírlia Silva Cardoso (2016)
The child visits the dentist nurture address the promotion of oral health with parents since the birth of babies, particularly when acting in an interdisciplinary way. The prevention of oral diseases, from the first month of life, is relevant because dental caries in the primary dentition is a predictor of risk for caries in the permanent dentition. This study aimed to analyze oral health actions developed in Childcare consultations of the Family Health Strategy in a primary health care clinic in the city of Fortaleza-CE. quantitative, observational, comparative cross-sectional study. The sample of 62 children with their parents / caregivers were divided into two groups: with and without dental dental childcare childcare. Held dental examination for children and interviews with parents / caregivers. Data were organized in Microsoft Excel® program in 2013, processed in EpiInfo version 7 and analyzed using the Student's t test and Mann-Whitney. For the analysis of variance was applied to the Bartlett test. The chi-square test was applied to qualitative variables and Fisher's exact test when expected values ​​lower than 5. The significance level for the tests was less than 5%. The study was approved by the Ethics Committee of the University of International Integration Lusophone African-Brazilian, under number 1269635. The opinion caries index was lower in the group with dental childcare (dmft 0.8) than in the group without childcare dental (dmft 2.2) aged 4 to 6 years old. In the assessment of knowledge and parental practices, group dental childcare demonstrated greater adherence and daily toothbrushing frequency (p = 0.01); greater number of children with 1st dentist appointment (p = 0.00); lower daily consumption of sugar and sweets, and greater consumption of vegetables and unsweetened juice. There was no statistically significant difference between the groups when the values ​​of the gingival changes were compared. The actions of the dentist in childcare consultations in the researched Unit have been effective in many ways, but some points need to be reviewed to ensure that the issues are better clarified with parents / caregivers.